Soft Continuous Mappings in Soft Closure Spaces - Ekram, S. T.; Majeed, R. N. (Iraqi Journal of Science, 2021)
Soft closure spaces are a new structure that was introduced very recently. These new spaces are based on the notion of soft closure operators. This work aims to provide applications of soft closure operators. We introduce the concept of soft continuous mappings and soft closed (resp. open) mappings, support them with examples, and investigate some of their properties.